2016
DOI: 10.1155/2016/6568347
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Creep Parameters of Linear Viscoelastic Materials

Abstract: Creep process of linear viscoelastic materials is described by the integral equation of Boltzmann-Volterra in which creep kernel is approximated by Rabotnov’s fractional exponential function. The creep equation contains four unknown parameters:α, singularity parameter;β, fading parameter;λ, rheological parameter; andε0, conditionally instantaneous strain. Two-stage determination method of creep parameters is offered. At the first stage, taking into account weak singularity properties of Abel’s function at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…It is known that the selection of kernel of the integral equation and determination of its parameters is one of the most responsible actions in the description of mechanical behavior of viscoelastic materials. As it has been said in our previous work [14], the most universal is creep kernel in the form of the fractional exponential function of Yu. N. Rabotnov [4][5][6]11].…”
Section: Introductionmentioning
confidence: 65%
“…It is known that the selection of kernel of the integral equation and determination of its parameters is one of the most responsible actions in the description of mechanical behavior of viscoelastic materials. As it has been said in our previous work [14], the most universal is creep kernel in the form of the fractional exponential function of Yu. N. Rabotnov [4][5][6]11].…”
Section: Introductionmentioning
confidence: 65%
“…Previous works [14,22,23] showed that an asphalt concrete creep curve-as with most viscoelastic materials-had three characteristic stages: stage I of unsteady-state creep with decreasing rate; stage II of steady-state creep with a constant (minimum) rate; and stage III of accelerating creep with increasing rate which precedes failure. The above studies presented test results of asphalt concrete for creep with relatively narrow ranges of stress variation.…”
Section: Creep Curvementioning
confidence: 99%
“…Therefore, the first and second stages of the creep curve are of main interest for mathematical description. The first stage of the creep curve for asphalt concrete was described with the use of Rabotnov's fractional exponential function [16] and was reported previously by the authors of Reference [14].…”
Section: Steady-state Creepmentioning
confidence: 99%
See 2 more Smart Citations